A Multi‐RNAi Microsponge Platform for Simultaneous Controlled Delivery of Multiple Small Interfering RNAs. (22nd December 2015) - Roh, Young Hoon; Deng, Jason Z.; Dreaden, Erik C.; Park, Jae Hyon; Yun, Dong Soo; Shopsowitz, Kevin E.; Hammond, Paula T.
Abstract: Packaging multiple small interfering RNA (siRNA) molecules into nanostructures at precisely defined ratios is a powerful delivery strategy for effective RNA interference (RNAi) therapy. We present a novel RNA nanotechnology based approach to produce multiple components of polymerized siRNA molecules that are simultaneously self‐assembled and densely packaged into composite sponge‐like porous microstructures (Multi‐RNAi‐MSs) by rolling circle transcription. The Multi‐RNAi‐MSs were designed to contain a combination of multiple polymeric siRNA molecules with precisely controlled stoichiometry within a singular microstructure by manipulating the types and ratios of the circular DNA templates. The Multi‐RNAi‐MSs were converted into nanosized complexes by polyelectrolyte condensation to manipulate their physicochemical properties (size, shape, and surface charge) for favorable delivery, while maintaining the multifunctional properties of the siRNAs for combined therapeutic effects. These Multi‐RNAi‐MS systems have great potential in RNAi‐mediated biomedical applications, for example, for the treatment of cancer, genetic disorders, and viral infections.